WHAT IS THE ECOLOGICAL APPROACH TO A LANGUAGE? (Proceedings of Southern Federal University. Philology, 2012)
Brusenskaya L.A.Keywords: ecology of language, linguistic ecology, standard and substandard, culture of speech, current language situation.The work studies the concepts of “ecological approach to a language” and “linguistic ecology”. The problems of the present state of the Russian language are discussed as well as the comparison of standard and non-standard varieties of the language, the problem of cultivation of public communication space.